Overlooked retained intraocular foreign body - Adžić-Zečević Antoaneta; Files-Bradarić Edita; Petrović Mirjana (Vojnosanitetski Pregled)
Introduction. The most common cause for litigation against ophthalmologists in a trauma case is a missed intraocular foreign body (IOFB). IOFBs cause internal eye damage, but some will come to rest in the posterior segment of the eye. Case report. We presented a 57-year-old male who was referred to the ophthalmologist due to decreased visual acuity in his left eye. Slit lamp examination of his left eye showed no pathological findings. Goldmann contact lens examination showed IOFB which was lying in the vitreous body in the inferior-temporal region. Retinal rupture was noticed at 7 o’clock. The optical coherence tomography (OCT) examination was performed and it showed atrophic macular area as well as decreased peripapillar retinal fiber layers thickness. Ultrasound showed the IOFB in vitreous body cavity. History revealed that the patient had an accidental trauma, 48 years ago, when an old bomb from World War II (WWII) exploded. Due to the decrease in visual acuity and fibrosis of the vitreous body surgical intervention was performed on his left eye (phacoemulsification with intraocular lens implantation, pars plana vitrectomy and instrumental extraction of foreign body). Conclusion. The intraocular foreign body (IOFB) was asymptomatic for 48 years. Symptoms depend on material and localization of the foreign body and the type of injury.